Enhancing collapse performance of vulnerable RC frames through steel Bracing: A FEMA P695 methodology study - Ali Sadeghpour; Giray Ozay (Ain Shams Engineering Journal)
Seismic assessments and statistical modeling of desired building responses have gained prominence in research. The FEMA P695 methodology facilitates evaluating structural safety based on collapse probabilities. An investigation into the performance of RC buildings designed according to the previous Iranian seismic code (Standard No. 2800–99) reveals a susceptibility to significant damage in far-field earthquakes. This study examines 1-, 3-, and 6-story RC frames, introducing concentric steel braces in various configurations as a cost-effective reinforcement method. Sixty archetypes undergo comprehensive analysis, including 15,800 nonlinear dynamic analyses to calculate collapse probabilities under total uncertainties. Insights into retrofitting vulnerable archetypes and seismic design parameters are obtained, leading to practical solutions and enhanced safety for old-designed building structures in seismic events.